2022
DOI: 10.1093/jtm/taac026
|View full text |Cite
|
Sign up to set email alerts
|

Multiple small pneumatoceles as a complication of a SARS-CoV-2 infection in a child from Myanmar

Abstract: During the COVID-19 pandemic, pneumatoceles caused by 2019-nCoV are easily neglected, particularly in children. Which may potentially increase the risk of pneumothorax and pulmonary infection, we need to pay special attention to the management of population migration, especially for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…There are increasing cases of COVID-19 patients with cavitary lung lesions, re-positive or long-term positive nucleic acid tests (Chen et al, 2020a;He et al, 2020;Qiao et al, 2020;Selvaraj and Dapaah-Afriyie, 2020;Lu et al, 2020a;Lu et al, 2020a;Wang et al, 2020b;Aggarwal et al, 2021;Afrazi et al, 2021;Chen et al, 2021;Egoryan et al, 2021;Jafari et al, 2021;Liang et al, 2021;Ozgur and Dogan, 2021;Wu et al, 2021;Zhu et al, 2021;Zoumot et al, 2021;He et al, 2022;Maccio et al, 2022). Lung cavities appear at a long-time interval from initial novel coronavirus infection, generally during the absorption phase of the disease, may have severer symptoms after initial recovery and also an increasing mortality rate (Aggarwal et al, 2021;Chen et al, 2021;Egoryan et al, 2021;He et al, 2022;Zoumot et al, 2021). Maccio et al performed autopsies on 35 COVID-19 patients and found that patients could still show diffuse alveolar damage 2 months after the initial diagnosis of COVID-19 (Maccio et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are increasing cases of COVID-19 patients with cavitary lung lesions, re-positive or long-term positive nucleic acid tests (Chen et al, 2020a;He et al, 2020;Qiao et al, 2020;Selvaraj and Dapaah-Afriyie, 2020;Lu et al, 2020a;Lu et al, 2020a;Wang et al, 2020b;Aggarwal et al, 2021;Afrazi et al, 2021;Chen et al, 2021;Egoryan et al, 2021;Jafari et al, 2021;Liang et al, 2021;Ozgur and Dogan, 2021;Wu et al, 2021;Zhu et al, 2021;Zoumot et al, 2021;He et al, 2022;Maccio et al, 2022). Lung cavities appear at a long-time interval from initial novel coronavirus infection, generally during the absorption phase of the disease, may have severer symptoms after initial recovery and also an increasing mortality rate (Aggarwal et al, 2021;Chen et al, 2021;Egoryan et al, 2021;He et al, 2022;Zoumot et al, 2021). Maccio et al performed autopsies on 35 COVID-19 patients and found that patients could still show diffuse alveolar damage 2 months after the initial diagnosis of COVID-19 (Maccio et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, being a potential factor in the formation of cystic or cavitary pulmonary lesion (Cardinal-Fernandez et al, 2017). But the existence of some mild COVID-19 cases with cystic or cavitary lung lesions relatively increases the possibility of SARS-CoV-2 directed lung lesions for the low chance of ARDS in mild cases (Chen et al, 2021;He et al, 2022). Some COVID-19 patients had an elevated level of inflammatory cytokines and biomarkers associated with bacterial co-infection (Mirzaei et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations